Treating limb apraxia via action semantics: a preliminary study. Issue 7 (9th August 2021) - Stoll, Harrison; de Wit, Matthieu M.; Middleton, Erica L.; Buxbaum, Laurel J.
ABSTRACT: Limb apraxia is evident in approximately 50% of patients after left hemisphere cerebral vascular accident (LCVA) and increases disability and caregiver dependence. Individuals with apraxia exhibit abnormalities in spatio-temporal aspects of gesture production and/or in knowledge of tool-related actions (action semantics). This preliminary study of three LCVA participants aimed to (i) explore the efficacy of a novel Action Network Treatment (ANT) that focused on improving the semantic association between tool actions and other types of tool knowledge, an intervention inspired by successful semantic network treatments in aphasia (e.g., Edmonds et al., 2009 ), and (ii) explore whether there are individuals with apraxia who benefit from ANT relative to a version of a comparatively well-studied existing apraxia treatment (Smania et al., 2006 ; Smania et al., 2000 ) that shapes gesture via focus on practicing the spatio-temporal aspects of gesture production (Tool Use Treatment or TUT). One participant demonstrated treatment benefits from both ANT and TUT, while another only benefited from TUT. These findings indicate that our novel semantic network strengthening approach to gesture training may be efficacious in at least some individuals with apraxia, and provide a foundation for future study of the characteristics of people with apraxia who benefit from each approach.